Protein delivery into cells using inorganic nanoparticle–protein supramolecular assemblies. (14th March 2018) - Scaletti, Federica; Hardie, Joseph; Lee, Yi-Wei; Luther, David C.; Ray, Moumita; Rotello, Vincent M.
Abstract : Direct intracellular delivery of proteins using inorganic nanoparticle–protein supramolecular assemblies. Abstract : The delivery of proteins into cells is a potential game changer for a wide array of therapeutic purposes, including cancer therapy, immunomodulation and treatment of inherited diseases. In this review, we present recently developed nanoassemblies for protein delivery that utilize strategies that range from direct assembly, encapsulation and composite formation. We will discuss factors that affect the efficacy of nanoassemblies for delivery from the perspective of both nanoparticles and proteins. Challenges in the field, particularly achieving effective cytosolar protein delivery through endosomal escape or evasion are discussed.